THEORETICAL RESEARCH ON THERMAL MODELING OF A HIGH POWER AUDIO DEVICE - Dr.Constantin D.Stanescu; Liliana Cainiceanu; Tudor Burlan (Fiabilitate şi Durabilitate)
This paper aims at analyzing the mechanism of heat transfer and consequently a thermal analysis. Data obtained provides a starting point in choosing solutions constructrive, mechanical and electrichal dynamic audio device prototype .A comprehensive approach allows optimization of device based on our maximum eficianta developed model and finite element analysis program using coupling possibilities in different conditions.